Global Climatic Changes and Risks to Food Security a Narrative Review - Shoaib, Nida; Ali, Syeda Tabeena; Rizvi, Sameera Ali; Juriasinghani, Manesha; Ahmed, Niaz (Pakistan Armed Forces Medical Journal, 2026)
A narrative review was conducted investigate the association of global climatic changes on food security, leading to malnutrition among women and children posed by environmental risks, using well-regarded databases such as Google Scholar, Pub Med, and Springer Link. Employing key terms like "climatic changes," "food security," "public health concern," "Global," and "Pakistan," the identification of relevant articles was followed. Through a particular selection process, where 20 studies were carefully chosen from an initial pool (January 2019 to 2023). The synthesis of these selected studies revealed evident correlations between climate variables (temperature, rainfall, humidity, and sunshine) and their distinct impact on crop production. Environmental risks emerged as difficult challenges to global food distribution systems, contributing significantly to an increase in disease burdens. Developing nations, particularly in regions such as Pakistan, confront difficult hurdles in food production, distribution, and nutrition, resulting in prevalent health challenges. These findings highlight the urgent commanding to fortify food systems, enhance infrastructure, and formulate policies geared towards fortifying global food security. Despite improvements in understanding the link between climatic changes and food security, determined research gaps persist. The continuing challenge lies in quantifying the complicated effect of change of climate on human health and the security of food. Additional studies were imperative to accomplish a comprehensive assessment of these effects at both global and local levels.